(untitled) (Fractal: Journal of Psychology, 2013)
This article discusses the emergence of Social Assistance Reference Centers (CRAS) highlighting the arts of governing that engender its creation. Also indicates that the CRAS, a strategic equipment of the National Social Assistance Policy (PNAS), is effect of crossing of diverse social practices, condensing into its emergency a biopolitical mode of management of populations, the neoliberal statecraft as art of government, the social assistance as field of knowledge and social practices and psychological practices. We point out that the CRAS can function as a control device and also as a field of production of deviations in social policies.